Prevalence of Helicobacter pylori vacA, cagA, iceA and oipA genotypes in Tunisian patients - Najjar Taoufik; Ben Mami Nabil; Fillali Azza; Labbene Mounir; Masmoudi Afef; Zribi Meriem; Fendri Chédlia; Ben Mansour Khansa; Meherzi Ahmed; Sfar Tahar; Burucoa Christophe (BMC, 2010)
Abstract Background Distinct virulence factors of H. pylori have been described: the vaculating cytotoxin (vacA), the cytotoxin associated gene (cagA), the induced by contact with epithelium factor Antigen (iceA gene) and the outer membrane protein oipA. In Tunisia, there are no data regarding the pattern of H. pylori genotypes; therefore, this prospective and multicentre study was the first to be done in Tunisia and aimed to investigate the prevalence of the vacA, cagA, iceA and oipA genotypes of H. pylori isolates from Tunisian patients with peptic ulceration, gastric cancer, MALT lymphoma and gastritis. Methods H. pylori was cultured from endoscopic biopsies obtained from 281 Tunisian patients. The vacA alleles, cagA, iceA and oipA genotypes were determined by PCR. Results The vacA s1m1, s1m2 and s2m2 were respectively found in 10.7%, 12.5% and 45.6% of strains. The s2m1 genotype was not detected in our study. The cagA was found in 61.6% of isolates. The iceA1 and the iceA2 genotypes were respectively isolated in 60.2% and in 16% of strains. The oipA genotype was detected in 90.8% of strains. Considering the vacA and iceA genotypes, the presence of multiple H. pylori strains in a single biopsy specimen was found respectively in 31.4% and 23.8%. The comparison between strains isolated from antrum and fundus showed that Tunisian patients were infected with two or more strains of different cagA, vacA, iceA and oipA genotypes and the discordance was respectively in 9.6%, 4.6%, 8.9% and 8.5% of strains. Conclusion Our results showed that in 46% (131 strains among 281), the H. pylori strains were highly virulent in relation of the three or four virulent factors they could carry. These finding were described before in the literature. Tunisian patients were colonized by one or multiple strains of H. pylori in the same time in relation of presence of vacA m1/m2 and iceA1/iceA2 in the same biopsy. The discordance between strains isolated from antrum and fundus was high, and it is in favour of multicolonization.